Modernity, Materiality and Domestic Technology: A Case Study of Cooling and Heating from South Australia. Issue 3 (26th May 2020) - Goodchild, Barry; Ambrose, Aimee; Berry, Stephen; Maye-Banbury, Angela; Moore, Trivess; Sherriff, Graeme
ABSTRACT: This paper uses oral history as an appropriate method to reveal how residents in the "green village" of Lochiel Park, South Australia, have changed their heating and cooling practises over their life courses. The analysis shows how concepts of modernity, largely drawn from Simmel, help analyze the narratives of the respondents and how these reveal both an increased reliance on technology in their life time and an increased involvement in the money economy. The narratives of the respondents at Lochiel Park express a paradox in which technological innovation has almost certainly enabled reduced energy use and reduced carbon emissions compared to the recent past, whilst also facilitating greater use of non-renewable energy sources compared to the period before the introduction of air conditioning. Based on the comments on residents, improved technology in building and in heating and cooling is likely to remain the most viable strategy towards sustainable thermal comfort.